Human gastric B cell responses can be induced by intestinal immunisation. (1st October 2001) - Quiding-Järbrink, M; Lönroth, H; Ahlstedt, I; Holmgren, J; Svennerholm, A-M
Abstract : BACKGROUND: In a previous study, we found that oral vaccination induces strong B cell responses in the stomach of Helicobacter pylori infected but not of uninfected individuals. In this study, we have evaluated the possibility of inducing gastric immune responses in H pylori infected volunteers by intestinal and gastric immunisation. METHODS: H pylori infected subjects were given two doses of an inactivated cholera vaccine, either intestinally via an endoscope approximately 30 cm distal to the pylorus sphincter or intragastrically as small droplets applied directly onto the stomach mucosa. Uninfected individuals received the vaccine by standard oral procedure. Vaccine specific antibody secreting cells in antral and duodenal biopsies were detected by the enzyme linked immunospot assay technique before and seven days after the second immunisation. RESULTS: Intestinal immunisations resulted in induction of vaccine specific gastric IgA secreting cells in five of eight volunteers. This immunisation schedule also gave rise to specific duodenal antibody secreting cells in seven of eight individuals. Local gastric immunisation resulted in the induction of specific B cells in the gastric mucosa of four of eight volunteers. Gastric antigen application also resulted in B cell responses in the duodenum in all volunteers. Uninfected volunteers receiving the vaccine perorally responded in the duodenum but not in the stomach. CONCLUSIONS: H pylori infection increases the ability of the gastric mucosa to serve as an expression site for intestinally induced B cell responses. These findings are of importance when designing a therapeutic H pylori vaccine, and based on our results such a vaccine can be delivered along the whole upper gastrointestinal tract.